2023
DOI: 10.1158/1940-6207.capr-22-0529
|View full text |Cite
|
Sign up to set email alerts
|

Racial, Ethnic, and Sex-based Disparities among High-risk Individuals Undergoing Pancreatic Cancer Surveillance

Abstract: Since its inception two years ago, the international, multicenter Pancreatic Cancer Early Detection (PRECEDE) Consortium has enrolled high-risk individuals (HRI) undergoing pancreatic ductal adenocarcinoma (PDAC) surveillance. Herein we aim to evaluate enrollment disparities in PRECEDE. Data on HRIs enrolled between May 2020 and March 2022 were collected, with HRIs defined as participants enrolled in PRECEDE meeting guideline-based criteria for PDAC surveillance. Of 1,273 HRIs enrolled, 1,113 were eligible for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…PRECEDE is committed to increasing participant diversity and equity in access to PC surveillance. 33 Our interim analysis showed that participants are overwhelmingly non-Hispanic White (89%). To increase enrollment diversity, we are onboarding centers that historically serve marginalized populations.…”
Section: Discussionmentioning
confidence: 85%
“…PRECEDE is committed to increasing participant diversity and equity in access to PC surveillance. 33 Our interim analysis showed that participants are overwhelmingly non-Hispanic White (89%). To increase enrollment diversity, we are onboarding centers that historically serve marginalized populations.…”
Section: Discussionmentioning
confidence: 85%
“…However, germline variants in other genes may be rare, making it challenging to assess their impacts in a cohort of this size. A larger-scale nationwide or international collaboration program, such as the PRECEDE Consortium [ 44 ], is needed to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for lack of participation in clinical research studies among African Americans include historical medical distrust of the research community, fear of research, and lack of information [ 23 ]. Racial disparity has also been revealed for high-risk individuals (genetic susceptibility or family history of pancreatic cancer) undergoing surveillance for pancreatic cancer through the Pancreatic Cancer Early Detection (PRECEDE) consortium; specifically, 87.7% of high-risk individuals self-identified as White, and only 2% as Black (total 1113 subjects) [ 24 ]. To our knowledge, this is the first study to document racial disparity in the management of patients with pancreatic cysts.…”
Section: Discussionmentioning
confidence: 99%